Synthesis and in vitro microsomal metabolism of 4-ethyl-5-(4-fluorophenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione and its potential metabolites - (:unkn) unknown (My University, 1998)
Although most triazoline-3-thione derivatives (cyclic thiosemicarbazides) are important compounds possessing some biological and pharmacological activities, no literature was found showing their metabolic reactions with hepatic microsomal preparations. We, therefore, planned to study the in vitro microsomal metabolism of a prototype, 4-ethyl-5-(4-fluorophenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione (A). The substrate (A) and its potential metabolites i.e. the corresponding dealkylation (A1), desulphuration (A2) and S-oxidation (A3) products were synthesized and characterized by spectral methods. The substrate and its potential metabolites were separated by a reverse phase HPLC. A was incubated with rat microsomal preparations fortified with NADPH and extracted into DCM; concentrated under a stream of N2 at 20 degrees C and analyzed by HPLC. The results indicated that A was metabolically inert and failed to produce the corresponding desulphuration (triazole-3-one) and S-oxidation (sulphenic acid) metabolites which would lead to pharmacological and toxicological alterations compared to the parent molecule. However, a small amount of dealkylated product (A1) was observed as a metabolite together with two unidentified metabolites.
Keywords: Animals; Rats; Triazoles; Hypoglycemic Agents; In Vitro Techniques; Biotransformation; Microsomes, Liver